2012
DOI: 10.12659/msm.882616
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich saline protects immunocytes from radiation-induced apoptosis

Abstract: SummaryBackgroundRadiation often causes depletion of immunocytes in tissues and blood, which results in immunosuppression. Molecular hydrogen (H2) has been shown in recent studies to have potential as a safe and effective radioprotective agent through scavenging free radicals. This study was designed to test the hypothesis that H2 could protect immunocytes from ionizing radiation (IR).Material/MethodsH2 was dissolved in physiological saline or medium using an apparatus produced by our department. A 2-[6-(4′-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
(21 reference statements)
0
33
0
Order By: Relevance
“…Mice received total-body radiation at the radiation center in the faculty of Naval Medicine, Second Military Medical University, China [19, 20], and the survival of mice was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Mice received total-body radiation at the radiation center in the faculty of Naval Medicine, Second Military Medical University, China [19, 20], and the survival of mice was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…IR causes bone marrow suppression, which suppress the hematopoietic stem and progenitor cells proliferation and differentiation (Wang et al, 2006;Meng et al, 2003). The rapidly dividing cells of the blood system, especially leukocytes and erythrocytes, and the immune organs and immune cells are highly sensitive to IR (Widel et al, 2003;Yang et al, 2012). Radiation significantly decreased peripheral blood WBC, platelet and RBC counts (Jiang et al, 2015;Suryavanshi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, a large portion of patients may fail in responding to the treatments or relapse after the treatment [22]. Recently, we found that hydrogen-rich solution can protect the immune system and accelerate the recovery of immunodeficiency induced by irradiation [23]. Meanwhile, our research determined that hydrogen can protect mice from GVHD by regulating TNF-α, IL-2, IL-10 [17].…”
Section: Discussionmentioning
confidence: 99%